Groundwater Quality Assessment Based on a Statistical Approach in Gaya District, Bihar - Ahmad, Shaz; Singh, Reena (Engineering, Technology & Applied Science Research, 2023)
India is one of the countries that face the serious problem of groundwater contamination. The current study’s main objective is to evaluate the quality of the groundwater in the Serghati and its surrounding region of the Gaya district and its suitability for drinking purposes. To achieve this aim, 75 groundwater samples from the 15 sampling sites were collected during the period from March to May 2022. We measured and analyzed the major physicochemical characteristics of the water and compared them to the World Health Organization (WHO) standards. With the help of the Water Quality Index (WQI), groundwater quality was assessed. According to the study results, 3 sites have a WQI value of more than 100, which is unsuitable for drinking. Correlation matrices were used to assess groundwater quality and the extent of the interdependencies of the various parameters. Principal Component Analysis (PCA) reduces the number of significant variables. Three principal components with a total variance of 73.53% were identified and used in the analysis. Overall, the result indicates that most areas’ water quality is good and safe for drinking.